2008
DOI: 10.1002/jctb.1955
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase and peroxidase production by Rhizopus oryzae strain ENHE obtained from pentachlorophenol‐contaminated soil

Abstract: BACKGROUND: The aim of this study was to investigate the ability of a zygomycete isolated from pentachlorophenol (PCP)-contaminated soil to produce peroxidase and phenoloxidase enzymes, and to determine the effect of tyrosine and PCP on the enzyme activities. The ability of the isolate to tolerate and remove PCP was also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
2
8
0
9
Order By: Relevance
“…In this work, maximal PCP removal was 92% of the initial PCP achieved at 72 h in cultures with 25 mg PCP L −1 , twice the initial concentration reported by León-Santiesteban et al [17]. Similar results have been found by Lu et al [35], who reported that the removal rate of phenolic compounds by free fungi is lower than the removal rate observed by immobilized P. chrysosporium fungi.…”
Section: Pcp Removal By R Oryzae Enhe Immobilized In Nylon Fibersupporting
confidence: 90%
See 3 more Smart Citations
“…In this work, maximal PCP removal was 92% of the initial PCP achieved at 72 h in cultures with 25 mg PCP L −1 , twice the initial concentration reported by León-Santiesteban et al [17]. Similar results have been found by Lu et al [35], who reported that the removal rate of phenolic compounds by free fungi is lower than the removal rate observed by immobilized P. chrysosporium fungi.…”
Section: Pcp Removal By R Oryzae Enhe Immobilized In Nylon Fibersupporting
confidence: 90%
“…oryze ENHE grew into nylon fiber impregnated with culture medium using the three conditions described in the methodology section: nylon at equilibrium sorption concentration impregnated with 3.0 mg PCP g −1 nylon; nylon at equilibrium sorption concentration impregnated with 3.0 mg PCP g −1 nylon plus 14 mg PCP L −1 , added to the culture medium used to impregnate the nylon fiber and as control nylon without PCP. Results showed that PCP inhibited growth of R. oryzae EHNE, as reported before by León-Santiesteban et al [17]. In the control culture, maximal biomass obtained was of 32 mg dry biomass g −1 nylon and, in cultures containing PCP, growth of R. oryzae ENHE was lower; maximal biomasss was of 18 and 15 mg biomass g −1 nylon in cultures with nylon cubes that contained PCP at equilibrium concentration and nylon at equilibrium concentration amended with 14 mg PCP g −1 nylon, respectively (Fig.…”
Section: R Oryzae Enhe Immobilization Into Nylon Fibersupporting
confidence: 82%
See 2 more Smart Citations
“…Szewczyk et al (2003) have also previously reported the isolation of zygomycete, Mucor ramosissimus from contaminated site that was capabale of tolerating and transforming 10 mg/L of PCP to tetrachlorohydroquinone (TCHQ). Leon-Santiesteban et al (2008) reported the isolation of tyrosinase and peroxidase producing zygomycete, Rhizopus oryzae from PCP contaminated soil that tolerated and removed 90% of initial PCP concentration (12.5%). Carvalho et al (2009) also showed that besides basidiomycetes or white rot fungi, zygomycetes such as Cunninghamella sp.…”
Section: Sd14 Sd19 Sd20mentioning
confidence: 99%